ANALISIS STRUKTUR DAN KOMPOSISI TUMBUHAN ASING INVASIF (INVASIVE SPECIES) PADA KAWASAN GUNUNG SIBUATAN DESA NAGALINGGA KECAMATAN MEREK KABUPATEN KARO SUMATERA UTARA - Ika Siti Noviyanti; Kartika Manalu; Melfa Aisyah Hutasuhut (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACTForeign Plants Invasive (Invasive Species) have the ability to grow and develop very quickly in an ecosystem so that they can cause environmental damage. The purpose of this research is to find out the structure and composition of weed plants in the area of Mount Sibuatan, Nagalingga Village, Brand District, Karo Regency, North Sumatra, using the checkered line method with 10 x 10 m in size plot which is placed by purposive sampling. Based on the research that has been carried out, it was obtained 20 families of 34 species with 452 individuals that divided into three levels of vegetation, namely trees, sapling and basic vegetation. The dominant families found consisted of the Asterceae and Euphorbiaceae families with 64.12% and 76.43% of percentage, the co-dominant families were the Poaceae and Rosaceae families with 17.06 and 16.20% of percentage. The highest Importance Value Index (INP) of the area is the species of Austroeupatorium inulifolium (Kunth) R.M.King & H. Rob with a value of 92.37. The invasive plants diversity index has moderate abundance of plant diversity. The spread patterns of invasive plants are include into the category of groups.